Efficacy of deferasirox in reducing and preventing cardiac iron overload in beta-thalassemia - Pennell, D.J.; Porter, J.B.; Cappellini, M.D.; El-Beshlawy, A.; Chan, L.L.; Aydinok, Y.; Elalfy, M.S.; Sutcharitchan, P.; Li, C.K.; Ibrahim, H.; Viprakasit, V.; Kattamis, A.; et al. (2010)
Cardiac iron overload causes most deaths in beta-thalassemia major. The efficacy of deferasirox in reducing or preventing cardiac iron overload was assessed in 192 patients with beta-thalassemia in a 1-year prospective, multicenter study. The cardiac iron reduction arm (n = 114) included patients with magnetic resonance myocardial T2* from 5 to 20 ms (indicating cardiac siderosis), left ventricular ejection fraction (LVEF) of 56% or more, serum ferritin more than 2500 ng/mL, liver iron concentration more than 10 mg Fe/g dry weight, and more than 50 transfused blood units. The prevention arm (n = 78) included otherwise eligible patients whose myocardial T2* was 20 ms or more. The primary end point was the change in myocardial T2* at 1 year. In the cardiac iron reduction arm, the mean deferasirox dose was 32.6 mg/kg per day. Myocardial T2* (geometric mean +/- coefficient of variation) improved from a baseline of 11.2 ms (+/- 40.5%) to 12.9 ms (+/- 49.5%) (+ 16%; P < .001). LVEF (mean +/- SD) was unchanged: 67.4 (+/- 5.7%) to 67.0 (+/- 6.0%) (-0.3%; P = .53). In the prevention arm, baseline myocardial T2* was unchanged from baseline of 32.0 ms (+/- 25.6%) to 32.5 ms (+/- 25.1%) (+ 2%; P = .57) and LVEF increased from baseline 67.7 (+/- 4.7%) to 69.6 (+/- 4.5%) (+ 1.8%; P < .001). This prospective study shows that deferasirox is effective in removing and preventing myocardial iron accumulation. This study is registered at http://clinicaltrials.gov as NCT00171821. (Blood. 2010; 115: 2364-2371)